An improved dry ash procedure for the detection of titanium dioxide in cattle feces. (18th April 2013) - Ohmori, Hideyuki; Nonaka, Itoko; Ohtani, Fumihiro; Tajima, Kiyoshi; Kawashima, Tomoyuki; KAJI, Yuji; Terada, Fuminori
Abstract We improved the dry ash procedure for detecting titanium dioxide (TiO2) in cattle feces containing chromium dioxide (Cr2O3). First, the effect of amount of sodium sulfate (Na2SO4) on the recovery of TiO2 from cattle feces that contained Cr2O3 was evaluated. Average recovery of TiO2 at the 2.5 g Na2SO4 level was significantly higher (P < 0.0001) than that at 0.75 g Na2SO4. Second, the effect of Cr2O3 concentration on the recovery of TiO2 of cattle feces by using two levels of Na2SO4 addition was examined. The recovery of TiO2 decreased with the increase in the amount of Cr2O3 at the 0.75 g Na2SO4 level but was consistently high at 2.5 g Na2SO4. Third, the recovery of Cr2O3 from cattle feces was checked. The recoveries of TiO2 and Cr2O3 were high enough at the 2.5 g Na2SO4 level. Fourth, the improved dry ash procedure (5 mL of concentrated H2SO4 and 2.5 g of Na2SO4 were used for sample digestion) was compared to the wet ash procedure. Average recovery of TiO2 by the improved dry ash procedure was significantly higher (P = 0.0077) than that by the wet ash procedure. Thus, the improved dry ash procedure can be used for TiO2 analysis in cattle feces containing Cr2O3.